The war girls - Alexander, V. S. (Kensington Publishing Corp., 2022)
It's not just a thousand miles that separates Hanna Majewski from her younger sister, Stefa. There is another gulf--between the traditional Jewish ways that Hanna chose to leave behind in Warsaw, and her new, independent life in London. But as autumn of 1940 draws near, Germany begins a savage aerial bombing campaign in England, killing and displacing tens of thousands. Hanna, who narrowly escapes death, is recruited as a spy in an undercover operation that sends her back to her war-torn homeland. In Hanna's absence, her parents, sister, and brother have been driven from their comfortable apartment into the Warsaw Ghetto. Sealed off from the rest of the city, the Ghetto becomes a prison for nearly half a million Jews, struggling to survive amid starvation, disease, and the constant threat of deportation to Treblinka. Once a pretty and level-headed teenager, Stefa is now committed to the Jewish resistance. Together, she, Hanna, and Janka, a family friend living on the Aryan side of the city, form a trio called The War Girls. Against overwhelming odds and through heartbreak they will fight to rescue their loved ones, finding courage through sisterhood to keep hope alive...